2017
DOI: 10.4049/jimmunol.1700579
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1–Driven Tolerogenic Programs Aggravate Yersinia enterocolitica Infection by Repressing Antibacterial Immunity

Abstract: is an enteropathogenic bacterium that causes gastrointestinal disorders, as well as extraintestinal manifestations. To subvert the host's immune response, uses a type III secretion system consisting of an injectisome and effector proteins, called outer proteins (Yops), that modulate activation, signaling, and survival of immune cells. In this article, we show that galectin-1 (Gal-1), an immunoregulatory lectin widely expressed in mucosal tissues, contributes to pathogenicity by undermining protective antibacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 78 publications
(119 reference statements)
1
28
0
Order By: Relevance
“…Within the immune system, Gal-1 is synthesized and secreted by a wide range of cells, including activated T and B cells (22,23), macrophages (24), Foxp3 + regulatory T cells (Tregs) (25,26), tolerogenic dendritic cells (DCs) (27,28), gd T cells (29), microglia (30), and myeloid-derived suppressor cells (29). Remarkably, Gal-1 expression is prominent in immuneprivileged sites, such as placenta (31,32), testis (33,34), and the eye (35), and is significantly up-or downmodulated in inflammatory conditions, including microbial infection (36)(37)(38), autoimmunity (27,39), allergy (40,41), cancer (19,29,(42)(43)(44), reproductive disorders (31,32,45,46), neurodegenerative diseases (30), and myocardial infarction (47). Interestingly, in experimental models, Gal-1 expression peaks during the recovery phase of autoimmune disease (27,30), indicating a major role for this lectin during resolution of inflammation.…”
Section: Gal-1: a Sweet Checkpoint In The Resolution Of Inflammatory mentioning
confidence: 99%
See 1 more Smart Citation
“…Within the immune system, Gal-1 is synthesized and secreted by a wide range of cells, including activated T and B cells (22,23), macrophages (24), Foxp3 + regulatory T cells (Tregs) (25,26), tolerogenic dendritic cells (DCs) (27,28), gd T cells (29), microglia (30), and myeloid-derived suppressor cells (29). Remarkably, Gal-1 expression is prominent in immuneprivileged sites, such as placenta (31,32), testis (33,34), and the eye (35), and is significantly up-or downmodulated in inflammatory conditions, including microbial infection (36)(37)(38), autoimmunity (27,39), allergy (40,41), cancer (19,29,(42)(43)(44), reproductive disorders (31,32,45,46), neurodegenerative diseases (30), and myocardial infarction (47). Interestingly, in experimental models, Gal-1 expression peaks during the recovery phase of autoimmune disease (27,30), indicating a major role for this lectin during resolution of inflammation.…”
Section: Gal-1: a Sweet Checkpoint In The Resolution Of Inflammatory mentioning
confidence: 99%
“…Moreover, microbes may co-opt inhibitory pathways to subvert host protective immunity (1). Recently we found that Gal-1driven tolerogenic circuits can repress protective immunity during infection with Yersinia enterocolitica, an enteropathogenic bacterium, by targeting local immunity, including NO production, NF-kB activation, and TNF synthesis, as well as systemic Th1 and Th17 responses (38). Similarly, in a model of Trypanosoma cruzi infection, Gal-1 fueled the activation of immunoregulatory circuits that hindered antiparasite immunity, particularly those involving differentiation of tolerogenic DCs and Tregs (37).…”
Section: Subverting Antimicrobial Responses By Co-opting the Gal-1 Pamentioning
confidence: 99%
“…Regarding bacterial infections, Gal4 and Gal8, two-CRD galectins, have been shown to recognize and kill bacteriaexpressing B− blood group antigens on their surface (54). Finally, pathogenic bacteria may also subvert recognition of host galectins to ensure successful attachment and invasion of target cells leading to alteration of immune responses (37). In conclusion, our study utilizes both in vitro and in vivo strategies to demonstrate that Gal1 favors the development of productive chlamydial infections by modulating attachment and internalization of bacteria into host cells via an N-glycandependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to bacterial infections, desialylation of airway epithelial cells by neuraminidases enhances adhesion of Streptococcus pneumoniae by facilitating Gal1 binding to specific glycans (36). Moreover, we recently found that the enteropathogenic bacterium Yersinia enterocolitica represses protective immune programs via Gal1-dependent pathways (37). Furthermore, in a model of Pseudomonas aeruginosa infection, Gal1 suppresses corneal immunopathology by limiting pathogenic Th17 responses (38).…”
mentioning
confidence: 99%
“…Impaired tolerance in the allogeneic setting might be due to enhanced cytotoxic T cell activity in the absence of Gal-1, while Gal-1 derived from NK cells was sufficient to induce apoptosis in activated T cells [ 42 ]. A tolerogenic role of Gal-1 has also been described in the context of bacterial infections [ 43 ] and in T. cruzi infected mice, in which Gal-1 is produced and secreted by B cells [ 44 ]. While Gal-1 is dispensable for normal development, at least in mice, it has important functions in modulating innate and adaptive immune mechanisms.…”
Section: Gal-1 Gene Dose Alters the Immune Phenotype And Tumour Anmentioning
confidence: 99%